Pengolahan Limbah Tambak Udang Terintegrasi Kultivasi Mikroalga dari Kawasan Pertambangan - Deviany Deviany; Triya Yuli Andini; Aji Hafiz Talaga; Andri Sanjaya; Feerzet Achmad; Dennis Farina Nury; Desi Riana Saputri (IPTEK The Journal of Engineering, 2026)
Microalgae have a high lipid content, making them a potential feedstock for biofuel production. In this study, microalgae isolated from the Tanggamus mining area was cultivated in liquid medium from shrimp aquaculture waste. The main objectives were to examine the growth of microalgae in shrimp aquaculture waste specifically in liquid waste, sediment waste, and a combination of both to assess whether these waste types can serve as effective cultivation media, and to evaluate the microalgae's adaptability as well as its role in mitigating environmental pollution. The microalgae were cultivated in the three different waste mediums, and the results were compared to a control medium using walne. The findings revealed that shrimp aquaculture sediment supported the highest biomass production, reaching 17.80 mg/L. The mixed media yielded 15.93 mg/L, while the walne control and liquid waste media produced 9.00 mg/L and 3.87 mg/L, respectively. Furthermore, post-cultivation analysis revealed an increase in nutrient concentrations, including nitrogen, phosphorus, and potassium, in the cultivation medium. The microalgae strain reduced BOD in shrimp aquaculture waste, especially in sediment. COD in liquid waste increased due to complex compounds and cell lysis. Lipid extraction from the microalgal biomass highlighting its potential as a feedstock for biodiesel production. These results suggest that shrimp aquaculture waste, particularly its sediment component, not only serves as a suitable medium for cultivating microalgae, but also contributes to environmentally sustainable practices by helping reduce aquatic pollution and promoting waste-to-resource conversion.